2022
DOI: 10.1039/d2ra04944a
|View full text |Cite
|
Sign up to set email alerts
|

Potent antibacterial activity of MXene–functionalized graphene nanocomposites

Abstract: (A) SEM and (B) HRTEM images of 75% F graphene:25% Ti3C2Tx nanocomposite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…[74] It is also well known that toxicity depends on MXene concentration: the higher MXene concentration, the greater the toxicity. [79,86,87] Considering their non-specific effect of "nanoknives", the molecular mechanism of action does not depend on concentration. Probably, the concentration-dependent effect is connected with inability of the cell recovery systems to cope with damages caused by MXenes at high concentrations.…”
Section: Toxicity and Biocompatibility Of Mxenesmentioning
confidence: 99%
See 2 more Smart Citations
“…[74] It is also well known that toxicity depends on MXene concentration: the higher MXene concentration, the greater the toxicity. [79,86,87] Considering their non-specific effect of "nanoknives", the molecular mechanism of action does not depend on concentration. Probably, the concentration-dependent effect is connected with inability of the cell recovery systems to cope with damages caused by MXenes at high concentrations.…”
Section: Toxicity and Biocompatibility Of Mxenesmentioning
confidence: 99%
“…Some studies have reported different antibacterial efficacy and, accordingly, toxicity against Gram-positive and Gramnegative bacteria. [79] It is associated with differences in the structure of bacterial cell envelope. In Gram-negative bacteria it consists of an outer lipopolysaccharide membrane, single layer of peptidoglycan, and an inner phospholipid membrane.…”
Section: Toxicity Of Mxenes and Mxene-containing Composites To Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 However, the exceptional electrical conductivity and electrochemical properties of MXenes render them promising candidates for exible electronics and planar devices. 21,22 According to a study by Li et al, 23 MXenes are intrinsically hydrophilic and have displayed higher electrical conductivity than solution processed graphene.…”
Section: Introductionmentioning
confidence: 99%
“…62 Recent advancements on photothermal conversion and antibacterial mechanisms pertaining to MXenes have been reported, as exemplied in the case of Ti 3 C 2 T x MXene with potent antibacterial activity against methicillin-resistant S. aureus (MRSA) and E. coli. 21,42 The design of novel MXene-based nanosystems with targeted antibacterial potentials can efficiently assist in controlling the bacterial infections along with elimination of bacterial resistance. 62 This review endeavored to delineate critical issues pertaining to the use of MXene-based composites against pathogenic and antibiotic-resistant bacteria, focusing on recent developments, important challenges, and future perspectives.…”
Section: Introductionmentioning
confidence: 99%